ASUHAN KEPERAWATAN NY. A DENGAN DIABETES MELITUS TIPE 2 DI RW 07 KELURAHAN KRUKUT KECAMATAN LIMO KOTA DEPOK - Megiantara Haruman (2023)
Background: Diabetes Mellitus or DM is a chronic disease that occurs when glucose levels in the blood are high or can be called hyperglycemia, this is caused by the body's inability to respond to insulin or the body's inability to produce insulin as a result of an autoimmune reaction and can also be caused by a lack of production insulin and the body's inability to respond to insulin, called insulin resistance, diabetic ulcers are one of the complications of diabetes mellitus, where the patient's wound healing process slows down resulting in many other injuries, this raises a feeling of concern for each sufferer of additional injuries or even the worst possibility involved in the act of amputation, this research was conducted to understand the concept of Nursing Care in Ny. A who experienced nursing problems with damage to the integrity of the skin in Ny. A with diabetes mellitus in Limo district. Research Methods: The research method used is a case study. Research Results: The nursing problem that arises is damage to the integrity of the skin where the nursing actions carried out are the treatment of diabetic foot wounds and education on the care of diabetic foot wounds. Conclusion: Application of nursing care Mrs. A is expected to be able to run according to the nursing care plan that achieves results from solving problems of damage to skin integrity as well as wound care education and clients can be cooperative during the nursing care process.